GE_GERICHTE A/1632/2024 vom 25. November 2024 - GE Cour de justice (2024)
REVENU DE LA FORTUNE IMMOBILIÈRE(DROIT FISCAL);VALEUR LOCATIVE;MONTANT LIBRE D'IMPÔT | LIFD.21.al1.letb; LIPP.24.al1.letb; LIFD.35.al1.letb; LIPP.39.al2.letc